(untitled) - Shahriyar; Khisro Kaleem Raza; Ahsan Ur Rehman (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
This study explored the challenges and issues the public sector school heads faced regarding to their authority to create learner-centered environment in their schools. The sample of the study consisted of 10 male school heads from District Swat, Khyber Pakhtunkhwa, Pakistan. Semi-structured interviews were used to collect the data from the research participants. The findings revealed a number challenges and issues the school heads faced to their authority. The school heads identified lack of professionalism among the school teaching and non-teaching staff, over-burdened by the office work to carry out effective monitoring of teaching-learning process, and lack of decision-making powers to take immediate decisions in the best interests of the students. The study has important implication for the management of schools by school heads, researchers and policy makers.